Lussazioni pure traumatiche coxofemorali - Gabellieri, P.; Castellani, I.; Gazzarri, F.; Dolfi, L.; Serpieri, S.; Pietrobono, D.; Bozzi, F. (Lo Scalpello - Journal, 2018)
PURE TRAUMATIC HIP DISLOCATIONPure hip dislocation represent a medical emergency that must be addressed immediately. Early diagnosis and timelytreatment are the goals to be targeted. A delay in treatment or diagnosis, as evidenced by many authors, exposepatients to complications such as arthrosis, necrosis of the femoral head, sciatic nerve injury and heterotopiccalcifications. For these reasons, reduction of dislocation should be treated as soon as possible, if the patient’sconditions allow so.